The application of ordinary differential operators to the study of the classical orthogonal polynomials - (:unkn) unknown (My University, 2015)
A Thesis submitted to the University of Dundee in application for the Degree of Doctor of Philosophy.
Complete thesis
This thesis is essentially concerned with the connections between the classical orthogonal polynomials and the differential operators associated with the differential equations of Gegenbauer, Legendre, Laguerre and Hermite